The Treatment of Clozapine-Withdrawal Delirium with Electroconvulsive Therapy - Modak, Anish; Åhlin, Arne (Case Reports in Psychiatry, 2017)
Clozapine, a commonly used atypical antipsychotic, can precipitate a severe withdrawal syndrome. In this report, we describe a case of delirium with catatonic features emerging after the immediate cessation of clozapine subsequent to concerns of developing neuroleptic malignant syndrome. After multiple treatments were found to be inefficacious, electroconvulsive therapy (ECT) was initiated, resulting in significant improvement. A literature search revealed six previous cases of clozapine-withdrawal syndromes of varied symptomatology treated with ECT. To our knowledge, the present case represents the first reported clozapine-withdrawal delirium treated successfully with ECT.